2022
DOI: 10.1161/circulationaha.121.057816
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Appropriate Shocks and Antitachycardia Pacing in Transvenous and Subcutaneous Implantable Defibrillators: Analysis of All Appropriate Therapy in the PRAETORIAN Trial

Abstract: Background: The PRAETORIAN trial showed non-inferiority of the subcutaneous implantable cardioverter-defibrillator (S-ICD) compared to the transvenous ICD (TV-ICD) with regard to inappropriate shocks and complications. In contrast to the TV-ICD, the S-ICD cannot provide antitachycardia pacing (ATP) for monomorphic ventricular tachycardia (VT). This pre-specified secondary analysis evaluates appropriate therapy and whether ATP reduces the number of appropriate shocks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 16 publications
0
39
0
1
Order By: Relevance
“…Whereas the main article reported on the rates of appropriate ICD shocks (ie, delivered for ventricular arrhythmias), it did not include detailed information on appropriate ICD therapies (shocks and antitachycardia pacing [ATP]) and did not provide results on the efficacy of ATP at terminating ventricular arrhythmias in the transvenous ICD group. 13 In this issue, Knops et al 14 report the results of a prespecified secondary analysis of the PRAETORIAN trial intended to examine appropriate ICD therapies and to determine whether ATP reduces the number of appropriate ICD shocks in the transvenous ICD group of the trial. They found that 86 of 426 (20.2%) patients in the S-ICD group received appropriate ICD therapy compared with 78 of 423 (18.4%) patients in the transvenous ICD group (P=NS).…”
Section: Article See P 321mentioning
confidence: 99%
See 4 more Smart Citations
“…Whereas the main article reported on the rates of appropriate ICD shocks (ie, delivered for ventricular arrhythmias), it did not include detailed information on appropriate ICD therapies (shocks and antitachycardia pacing [ATP]) and did not provide results on the efficacy of ATP at terminating ventricular arrhythmias in the transvenous ICD group. 13 In this issue, Knops et al 14 report the results of a prespecified secondary analysis of the PRAETORIAN trial intended to examine appropriate ICD therapies and to determine whether ATP reduces the number of appropriate ICD shocks in the transvenous ICD group of the trial. They found that 86 of 426 (20.2%) patients in the S-ICD group received appropriate ICD therapy compared with 78 of 423 (18.4%) patients in the transvenous ICD group (P=NS).…”
Section: Article See P 321mentioning
confidence: 99%
“…Patients with a transvenous ICD and appropriate ICD therapy appeared to be at an increased relative risk of experiencing electric storms compared with the S-ICD group, but this comparison did not reach statistical significance. 14 The authors are to be commended for conducting this analysis, which provides helpful insights into the PRAE-TORIAN trial and sheds light on important and clinically relevant issues related to appropriate ICD therapies. Their analysis has several strengths, including the use of randomized clinical trial data, protocol-driven programming of ICDs, and central adjudication of events and electrograms.…”
Section: Article See P 321mentioning
confidence: 99%
See 3 more Smart Citations